Cultivating a Lifelong Learning for Reading: A Conceptual Framework for Enhancing Children’s Literacy Through Community Libraries in Uganda - Nalumansi, Mary; Kaddu, Sarah (Ghana Library Journal, 2024)
Purpose: This paper investigated the current status of reading among children within the Nambi SseppuuyaCommunity Resource Centre in Uganda in relation to their reading requirements, reading profile and the difficulties encountered when learning to read.Methods: This study was conducted in line with an interpretivist paradigm and a qualitative case study research approach. Focus group discussions were conducted with 80 children between the ages 6 to 13 years. Pattern matching analysis was also conducted to help establish patterns regarding noteworthy findings from the data. Findings: The study showed that having access to reading materials of all types, read aloud activities, and parental involvement are key components of good literacy skills. However, factors like limited access to quality reading materials, language issues, and location of the library hamper effective learning of literacy. From the observations, children urged parents to provide books in their native languages and interesting books to create reading interest.Practical Implications: The study suggested that more free or low cost books and books in different languages should be made available, and most importantly, reading environments should be put in place to encourage the habit of reading. Further, the paper presents the Community Library-Driven Reading Culture Framework (CL-DRCF) to overcome the identified challenges towards enhancing the literacy engagement among children at the resource centre.